On the Scotch branch of the Poor Removal question - Hancock, W. Neilson (Statistical and Social Inquiry Society of Ireland, 1881)
In the report of the Select Committee on Poor Removal of 1879 there is a very marked difference in the way in which the Scotch and English branch of the question was dealt with.
Read before the Society, 6 July 1880
Keywords: Poor removal; Poverty; Migration; 314.15